Aymptotic distribution of OLS estimators in linear regressions with strong-mixing explanatory variable and trend - Huaranga Narvajo, Juvert (2018)
The aim of the paper is to obtain MCO estimators in a linear regression with strong-mixing explanatory variables and trend. Strong-mixing process offers a greater degree of generalization given that stationary and non-stationary regressors can be included. To obtain the asymptotic distribution results from real analysis and probability theory for dependent processes are used. Unlike classical results for estimators in linear models the derived asymptotic distribution is not normally standard and depends on the parameters of the variables.